Arts and cultural leadership in Asia - Caust, Josphine (London : Routledge, 2015)
'Arts and cultural activity in Asia is increasingly seen as important internationally, and Asia's growing prosperity is enabling the full range of artistic activities to be better encouraged, supported and managed. This book presents a range of case studies of arts and cultural leadership across a large number of Asian countries. Besides examining different cultural frameworks and contexts, the book considers different cultural approaches to leadership, discusses external challenges and entrepreneurialism, and explores the impact of politics. Throughout, the book covers different art forms, and different sorts of arts and cultural organisations'--
Includes bibliographical references and index.
Keywords: Arts -- Asia; Arts -- Asia -- Management; Art and state -- Asia; Asia -- Cultural policy